Pelatihan Analisa Data Penelitian Qualitative Menggunakan N-Vivo dalam Upaya Meningkatkan Kapasitas Research dan Literasi Digital Dosen di Era Pandemi Covid19 - Arif Zunaidi; Sulistyowati Sulistyowati; Fachrial Lailatul Maghfiroh (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Informatika Indonesia Surabaya, 2022)
The pandemic makes many things difficult to do because of the restrictions on community mobilization in interacting. The world of higher education is one of those affected by the pandemic. Education, research, and community service activities have decreased, which has an impact on the quality and quantity of the research results of the lecturers. In order to increase the capacity of educators and researchers and at the same time serve the community, an analytical tool is needed that can make it easier for lecturers to find and determine the results of the analysis of the data that has been collected. This service activity takes the form of a workshop on the use of the N-Vivo application, which is used to increase the capacity of lecturers as researchers as well as to improve literacy, particularly in the creation of scientific works. This workshop was held for two days, Monday and Tuesday, November 8—9, 2021. In addition, this activity was also held in two places. The first is at the Viva Kediri hotel, and the second is at the TIPD hall on the 2nd floor of IAIN Kediri. The workshop was guided by Prof. Dr. Achmad Nurmandi, M.Sc, along with 3 assistants. On the first day, the material given was on the use of the Mendeley application in finding and making journal citations and the use of the Vosviwer application to group data related to the number of journal citations. Meanwhile, on the second day, the speaker focused on the use of the N-Vivo application. Overall, the activity went smoothly. However, several obstacles were found, including an unstable wifi network, especially on the first day. Meanwhile, another obstacle is the need for high-spec laptops, so many participants are constrained from being able to use the N-Vivo application. The enthusiasm of the participants was also high. The level of satisfaction of workshop participants is also high. It is hoped that this activity can be carried out again to increase understanding of using the application.